Clinical features and outcome of multisystem inflammatory syndrome in children (MIS-C) patients in northwest general hospital and research center Peshawar - Rehman, Fatima; Sethi, Bilal; Iqbal, Sahar; Noreen, Saima; Hussain, Saba; Rehman, Aziz Ur (International Journal of Pathology, 2025)
Background: Multisystem Inflammatory Syndrome in Children (MIS-C) is a post–COVID-19 hyperinflammatory condition with multisystem involvement. Due to limited regional data, this study assessed the clinical features and outcomes of MIS-C in children admitted to Northwest General Hospital, Peshawar. Methods: A six-month descriptive cross-sectional study was conducted after ethical approval. Seventy-nine patients aged 0–19 years meeting WHO/CDC MIS-C criteria were included through sequential sampling. Clinical presentation, laboratory findings, treatment, and outcomes were recorded and analyzed using SPSS 23. Results were reported as frequencies, percentages, and means where appropriate. Results: Most patients were 6–12 years old (44.3%) and female (63.3%). Prior COVID-19 exposure was documented in 69.6%, and 72.2% had elevated antibody titers. Common symptoms were reduced oral intake (59.5%), rash (45.6%), conjunctival congestion (40.5%), vomiting (40.5%), abdominal pain (29.1%), hypotension (35.4%), and tachycardia (32.9%). CRP (74.7%), ESR (49.4%), and AST (51.9%) were the most frequently elevated markers. Cardiac dysfunction occurred in 7.6% of cases. Intravenous immunoglobulins (IVIG, 94.9%) and steroids (72.2%) were the main treatments; 36.7% required inotropes and 3.8% mechanical ventilation. Mortality was 21.5%, significantly higher among those with concurrent measles. Conclusion: MIS-C commonly involved gastrointestinal, cardiovascular, and mucocutaneous systems. Most children improved with timely Intravenous immunoglobulins, steroid therapy, and supportive care, but coexisting measles was associated with markedly poorer outcomes